Transatlantic Conversations : Nineteenth-Century American Women's Encounters with Italy and the Atlantic World - Lueck, Beth L. (Book collections on Project MUSE., 2016)
How American women authors interacted as writers, activists, and reformers in Europe and the Caribbean during the nineteenth century.